Durable Clinical Effectiveness With Paclitaxel-Eluting Stents in the Femoropopliteal Artery: 5-Year Results of the Zilver PTX Randomized Trial - Dake, Michael D; Ansel, Gary M; Jaff, Michael R; Ohki, Takao; Saxon, Richard R; Smouse, H Bob; Machan, Lindsay S; Snyder, Scott A; O'Leary, Erin E; Ragheb, Anthony O; Zeller, Thomas (Circulation (New York, N.Y.), 2016)
This randomized controlled trial evaluated clinical durability of Zilver PTX, a paclitaxel-coated drug-eluting stent (DES), for femoropopliteal artery lesions. Outcomes compare primary DES versus percutaneous transluminal angioplasty (PTA), overall DES (primary and provisional) versus standard care (PTA and provisional Zilver bare metal stent [BMS]), and provisional DES versus provisional BMS. Patients with symptomatic femoropopliteal artery disease were randomly assigned to DES (n=236) or PTA (n=238). Approximately 91% had claudication; 9% had critical limb ischemia. Patients experiencing acute PTA failure underwent secondary randomization to provisional BMS (n=59) or DES (n=61). The 1-year primary end points of event-free survival and patency showed superiority of primary DES in comparison with PTA; these results were sustained through 5 years. Clinical benefit (freedom from persistent or worsening symptoms of ischemia; 79.8% versus 59.3%, P<0.01), patency (66.4% versus 43.4%, P<0.01), and freedom from reintervention (target lesion revascularization, 83.1% versus 67.6%, P<0.01) for the overall DES group were superior to standard care in nonrandomized comparisons. Similarly, clinical benefit (81.8% versus 63.8%, P=0.02), patency (72.4% versus 53.0%, P=0.03), and freedom from target lesion revascularization (84.9% versus 71.6%, P=0.06) with provisional DES were improved over provisional BMS. These results represent >40% relative risk reduction for restenosis and target lesion revascularization through 5 years for the overall DES in comparison with standard care and for provisional DES in comparison with provisional BMS. The 5-year results from this large study provide long-term information previously unavailable regarding endovascular treatment of femoropopliteal artery disease. The Zilver PTX DES provided sustained safety and clinical durability in comparison with standard endovascular treatments. URL: http://www.clinicaltrials.gov. Unique identifier: NCT00120406.